Neurofascin and Compact Myelin Antigen-Specific T Cell Response Pattern in Chronic Inflammatory Demyelinating Polyneuropathy Subtypes - Diederich, Jan-Markus; Staudt, Maximilian; Meisel, Christian; Hahn, Katrin; Meinl, Edgar; Meisel, Andreas; Klehmet, Juliane (Frontiers in Neurology, 2018)
Objective The objective of this study is to investigate whether chronic inflammatory demyelinating polyneuropathy (CIDP) and its subtypes differ in their type 1 T-helper (TH1) cell response against nodal/paranodal neurofascin (NF186, NF155) as well as myelin protein zero (P0 180–199) and myelin basic protein (MBP 82–100). Methods Interferon-gamma (IFN-γ) enzyme-linked immunospot assay was used to detect antigen-specific T cell responses in 48 patients suffering typical CIDP (n = 18), distal acquired demyelinating polyneuropathy (n = 8), multifocal acquired demyelinating sensory and motor polyneuropathy (MADSAM; n = 9), and sensory CIDP (n = 13) compared to other non-immune polyneuropathy (ON; n = 19) and healthy controls (n = 9). Results Compared to controls, MADSAM and sensory CIDP patients showed broadest IFN-γ T cell responses to all four antigens. Positive IFN-γ responses against two or more antigens were highly predictive for CIDP (positive predictive value = 0.95) and were found in 77% of CIDP patients. Patients with limited antigen-specific response were females, more severely affected with neuropathic pain and proximal paresis. The area under the receiver operating characteristics curve (AUC) of NF186 in MADSAM was 0.94 [95% confidential interval (CI) 0.82–1.00] compared to ON. For sensory CIDP, AUC of P0 180–199 was 0.94 (95% CI 0.86–1.00) and for MBP 82–100 0.95 (95% CI 0.88–1.00) compared to ON. Conclusion Cell-mediated immune responses to (para)nodal and myelin-derived antigens are common in CIDP. TH1 response against NF186 may be used as a biomarker for MADSAM and TH1 responses against P0 180–199 and MBP 82–100 as biomarkers for sensory CIDP. Larger multicenter studies study are warranted in order to establish these immunological markers as a diagnostic tools.